Technology application in the tourism and hospitability industry - Gilson, Paula (USA Willford Press, 2023)
Travel technology refers to the use of IT (information technology) or ICT (information and communication technology) in the travel, hospitality and tourism industry. Most significant examples of technological applications in tourism and hospitality comprise online travel and tourism agencies, flight tracking, and programs where tourists review their experiences. There are numerous benefits of travel technology such as saving time, surpassing the barriers of luggage and reducing paper work. Technology has directly aided in increasing operational efficiency, lowering costs, and improving consumer experience and services in tourism. This book includes some of the vital pieces of work being conducted across the world, on various topics related to the application of technology in tourism and hospitality industry. It includes contributions of experts, which will provide innovative insights into this field.
Keywords: Tourism--Technoloy innovations; Hospitality industry--Technological innovations; Tourism--Data processing